2016
DOI: 10.1519/ssc.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Neuromuscular Training in Youth Athletes. Part II: Strategies to Prevent Injuries and Improve Performance

Abstract: THE SECOND PART OF THIS REVIEW PROVIDES A FLEXIBLE APPROACH TO INTEGRATIVE NEUROMUSCULAR TRAINING (INT) WITH THE GOALS TO IMPROVE INJURY RESILIENCE AND TO ENHANCE SPORT AND MOTOR PERFORMANCE ABILITIES IN YOUTH POPULATIONS. THE PROPOSED MODEL OF INT IN THIS MANUSCRIPT PRESENTS 6 ESSENTIAL COMPONENTS: DYNAMIC STABILITY (LOWER LIMB AND CORE), STRENGTH, PLYOMETRICS, COORDINATION, SPEED AND AGILITY, AND FATIGUE RESISTANCE. THE DEVELOPMENT OF THESE 6 CAPACITIES ARE INTEGRAL IN ESTABLISHING AN IMPORTANT FOUNDATION BY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 86 publications
1
67
0
9
Order By: Relevance
“…Focus on neuromuscular plyometrics (i.e., vertical and horizontal jumping) and eccentric training (i.e., elastic bands), to maintain some key adaptations related to the stretch-shortening cycle, strength and power performance. Adaptations of the stabilizer muscles as an indispensable element and facilitator of the efficient sensorimotor action of any act is also extremely important [46,47]; -Educate the athlete about nutrition, supplementation (especially Vitamin D, zinc and proteins) and hydration in isolation conditions, and about strategies to control body mass and body composition [5,36,48,49]. It is important to consume food to fight off viral infections, thus advising against lower carbohydrate/intermittent fasting approaches is likely important [50]; -Organize mental fatigue monitoring and mental training (mental self-help techniques and/or the support of a psychologist by telecommunication) [51]; -Provide adequate methods of recovery (supplementation, sleep, breathing and meditation exercises, self-massage, myofascial relaxation, stretching, low back heat, etc.)…”
Section: Window Of Opportunity During the Isolationmentioning
confidence: 99%
“…Focus on neuromuscular plyometrics (i.e., vertical and horizontal jumping) and eccentric training (i.e., elastic bands), to maintain some key adaptations related to the stretch-shortening cycle, strength and power performance. Adaptations of the stabilizer muscles as an indispensable element and facilitator of the efficient sensorimotor action of any act is also extremely important [46,47]; -Educate the athlete about nutrition, supplementation (especially Vitamin D, zinc and proteins) and hydration in isolation conditions, and about strategies to control body mass and body composition [5,36,48,49]. It is important to consume food to fight off viral infections, thus advising against lower carbohydrate/intermittent fasting approaches is likely important [50]; -Organize mental fatigue monitoring and mental training (mental self-help techniques and/or the support of a psychologist by telecommunication) [51]; -Provide adequate methods of recovery (supplementation, sleep, breathing and meditation exercises, self-massage, myofascial relaxation, stretching, low back heat, etc.)…”
Section: Window Of Opportunity During the Isolationmentioning
confidence: 99%
“…Moreover, short shuffling moves in volleyball training, which involve leg coordination [45], could significantly contribute to better results in KTK transfer on platforms. NMT represents an integrative model that includes multiple components (e.g., strength, balance, power, skill development) [46]. However, our program ( Table 2) did not include balance exercises, which could be the reason for nonsignificant effects in KTK walking backward test.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fort-Vanmeerhaeghe et al [11] developed a classification of the INT components that included two blocks: (a) The first block focused on the development of fundamental movement skills, which includes coordination, strength, plyometric, agility, dynamic stability, speed, and fatigue resistance training, and (b) in the second block sport-specific movement skills were included [11]. It is suggested that all these contents must be exercised in order to improve performance and reduce injury risks.…”
Section: Introductionmentioning
confidence: 99%
“…By coordination, within the fundamental movement skills, authors usually refer to locomotor, manipulation, and stability skills (variety of movements and multitasking, including unanticipated reactions). It is believed that these abilities allow control and optimize different sport-specific movements, thus decreasing the injury risks in youth athletes [11]. Additional aspects, such as strength, have been extensively analyzed in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation